Public security in Brazil: Efficiency and technological gaps - Francisco Soares de Lima; Emerson Marinho (EconomiA, 2017)
This article analyzes the technical efficiency, the Total Factor Productivity (TFP) and the technological gap in public security services in Brazilian States. The order—m frontier is used for results estimation. The TFP variation is built by decomposing the Malmquist productivity index into technical efficiency, scale efficiency and technological variation. More than 50% of the federative units were considered technically inefficient. Out of the 27 federative units, 12 presented a positive total productivity while all others suffered total productivity losses. Productivity gains in public security are more related to scale aspects than to efficiency improvements and technological progress. – – Este artigo analisa a eficiência técnica, a Produtividade Total dos Fatores (PTF) e a defasagem tecnológica nos serviços de segurança pública nos Estados brasileiros. A fronteira da ordem-m é usada para estimar os resultados. A variaç\~ao da PTF é calculada pela decomposiç\~ao do índice de produtividade de Malmquist em termos da variaç\~ao da eficiência técnica, variaç\~ao da eficiência de escala e da variaç\~ao tecnológica. Mais de 50% das unidades federativas foram consideradas tecnicamente ineficientes. Das 27 unidades federativas, 12 apresentaram variaç\~ao da produtividade total positiva, enquanto todas as outras sofreram perdas de produtividade total. Os ganhos de produtividade na segurança pública est\~ao mais relacionados com aspectos de escala do que com a melhoria da eficiência e o progresso tecnológico.
Keywords: 330; Public security; Criminality; Productivity; Efficiency and technology